Study on fracture toughness of carbon-carbon composites at low temperatures. (2022) - Kumar, B.V. Sunil; Londe, Neelakantha V.; Kumar, Mohan; Lokesha, M.; Vasantha Kumar, S.N.; Surendranathan, A.O.
Highlights: The Carbon-Carbon Composites (C-CC) has proven to be the most efficient material in extreme temperature situations. Although C-CC is normally utilized at very high service temperatures, recently it has been necessary to explore these in low temperature circumstances. The present experimental study explores the influence of low temperature on the fracture toughness of C-CC. The low temperatures test of the samples has been done at a temperature range between −10 °C and −40 °C. The results demonstrate that the fracture toughness value consistently raised as the temperature dropped. Abstract: Carbon-carbon composites (C-CC), employed as composites in space and other industries for their outstanding properties. In extreme temperatures, the C-CC has proved to be the most efficient material. C-CC is one of the top thermal quality high-temperature materials such as high-temperature stability, excellent thermal conductivity, and low-temperature expansion coefficients. C-CC brake disks are highly demanded in aviation, trains, trucks, even race vehicles. Although C-CC is normally utilized at very high service temperatures, recently it has been necessary to explore these in low-temperature circumstances as components must also pass through low-temperature conditions in modern applications. In developing engineering structures, materials and systems for their technical safety, durability, and reliability, fractures and damage prevention and evaluation have an important role to play. Fracture toughness means quantifying the resistance of the fracture when a crack occurs. The present experimental study explores the influence of low temperature on the fracture toughness of C-CC. The low temperatures test of the samples has been done at a temperature between −10 °C and −40 °C. The results demonstrate that the fracture toughness value consistently raised as the temperature dropped. The Fluctuation began at a −10 °C from 2 % with a forecast of −40 °C to 32 %.